2017
DOI: 10.1097/md.0000000000008657
|View full text |Cite
|
Sign up to set email alerts
|

Urgent laparoscopic ureterolithotomy for proximal ureter stones accompanied with obstructive pyelonephritis

Abstract: To evaluate the safety and efficacy of retroperitoneal laparoscopic ureterolithotomy (RLU) in the treatment of proximal ureteral stones accompanied with obstructive pyelonephritis without preoperative drainage.We retrospectively reviewed 21 cases of proximal ureteral stones with infected kidney undergoing RLU between July 2013 and September 2016. Stone-induced obstructive infected hydronephrosis was diagnosed using blood and urine tests and imaging modalities. Empirical effective broad spectrum antibiotic ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…The most common indication of TPLU in our study was primary procedure for impacted upper stones in 51.7% of patients, followed by failed ESWL in 35%, and failed URS in 13.3% of cases. Our results are similar to previous papers such as those of Huan et al(14), El-Moula et al(2), and Nasseh et al(15). In our report, 61.7% of patients had severe HDN.…”
supporting
confidence: 93%
“…The most common indication of TPLU in our study was primary procedure for impacted upper stones in 51.7% of patients, followed by failed ESWL in 35%, and failed URS in 13.3% of cases. Our results are similar to previous papers such as those of Huan et al(14), El-Moula et al(2), and Nasseh et al(15). In our report, 61.7% of patients had severe HDN.…”
supporting
confidence: 93%
“…The relatively low incidence of infection in RPLU group may be associated with no elevated intra-pelvic pressure during the whole procedure. [24,25] KUB plain film showed that abnormal position of DJ stent occurred in both groups on the first day after operation. The cases with abnormal position of DJ stent in RPLU group was more than that in MPCNL group.…”
Section: Discussionmentioning
confidence: 94%
“…Third, purulent urine was found after percutaneous nephrostomy in three patients and staged operation was performed. The relatively low incidence of infection in RPLU group may be associated with no elevated intra-pelvic pressure during the whole procedure [24,25] …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Active intervention is needed to assist in removing stones, especially stones that have caused obstruction or are large in size. Two active interventions can be shockwave lithotripsy (SWL) or ureteroscopy (URS) [1], [2].…”
Section: Introductionmentioning
confidence: 99%